Ensino e aprendizagem de guitarra elétrica no Triângulo CRAJUBAR – CE - Pinheiro, Cicero Wagner Oliveira (2017)
The aim of this dissertation was to understand pedagogical and methodological practices in the teaching and learning of electric guitar in the CRAJUBAR triangle and to foster those considered fundamental for a teaching of democratic music. For that, it was necessary, besides investigating some spaces of teaching and learning of electric guitar in the course of Graduation in Music of the UFCA, to present a brief history of the electric guitar in the CRAJUBAR under the perspective of the life history of some agents. In order to illuminate the reflections, this research used as a theoretical reference the Ecology of Knowledge of Maria Cândida Moraes, the praxiology of Pierre Bourdieu and some ideas and proposals of Maura Penna on the democratization of access to art and culture. It is a qualitative research and the methodological procedures adopted are the life history in formation and studies of the ethnographic type. The work presented an interesting organization of the studies of the guitar from six topics: knowledge of the arm, technique, music reading, harmony, improvisation and repertoire; From this organization, the following pedagogical practices and methodological resources can be used: System 5 (CAGED), musical appreciation, “pick up songs from the ear”, transcription in score, composition - in a broad sense -, study and repertoire performance that contemplate a wide variety of genres and musical styles, from popular music to the erudite, use of metronome, playbacks, audios, videos, video lessons and music recording. We also emphasize Shared Musical Learning as an excellent methodological proposal for the teaching and learning of electric guitar in collective contexts.